2017
DOI: 10.1002/bem.22088
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of wheat seed vitality by dielectric barrier discharge plasma treatment

Abstract: Influences of discharge voltage on wheat seed vitality were investigated in a dielectric barrier discharge (DBD) plasma system at atmospheric pressure and temperature. Six different treatments were designed, and their discharge voltages were 0.0, 9.0, 11.0, 13.0, 15.0, and 17.0 kV, respectively. Fifty seeds were exposed to the DBD plasma atmosphere with an air flow rate of 1.5 L min for 4 min in each treatment, and then the DBD plasma-treated seeds were prepared for germination in several Petri dishes. Each tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…e NTP treatment caused cracks occurring on wheat grain surface, which led to the improvement of water uptake, subsequently benefiting its germination [43]. After NTP treatment, the mean water uptake was 41% in the control sample and 57% in the exposed one [44]. Similar etching effect, resulting in the improvement of its water absorption capacity, was reported by Li et al [45].…”
Section: Surface Property Affectionsupporting
confidence: 54%
See 3 more Smart Citations
“…e NTP treatment caused cracks occurring on wheat grain surface, which led to the improvement of water uptake, subsequently benefiting its germination [43]. After NTP treatment, the mean water uptake was 41% in the control sample and 57% in the exposed one [44]. Similar etching effect, resulting in the improvement of its water absorption capacity, was reported by Li et al [45].…”
Section: Surface Property Affectionsupporting
confidence: 54%
“…Maximum increase of plant length was achieved by 11% for 6 or 9 min exposures. e significant increase of shoot length, root length, dry weight, and fresh weight of wheat grains was described also in [44].…”
Section: Seed Germination and Seedling Initial Growthmentioning
confidence: 82%
See 2 more Smart Citations
“…Several studies have demonstrated a favourable effect of cold plasma treatment on seed germination and plant yields of a range of important crops, including wheat 11,24 , rice 22 , barley 25 , oats 26 , soybean 27 , spinach 28 , oil seed rape 29 , green onion 30 , chick peas 31 and cucumber 32 . For example, a study by Jiang, et al .…”
Section: Discussionmentioning
confidence: 99%